ATTITUDES OF KLIMAKTERIUM’S WOMEN IN DEALING MENOPAUSE PERIOD AT JIMUS VILLAGE POLANHARJO DISTRICT KLATEN REGENCY - Emi Apriyanti; Sumantri .; Arum Sekar Tanjung (STIKES DUTAGAMA KLATEN, 2012)
Background : Menopause is a normal phase in the life of women. Arise of problems experienced by klimakterium’s women, causing many kind of responses and different judgments of the individual because of different knowledge of the individual so that the result attitude was different. At Jimus village there are 5 of 10 mothers have a negative attitude in the deal of menopause, some women are resigned or ignore the complaint their experienced. Objective : To determine the attitudes of klimakterium’s women of dealing menopause period at Jimus Village Polanharjo District Klaten Regency. Method : The research is descriptive research with quantitative descriptive research design. The approach used is a cross sectional. Sample was take by quota sampling technic that use 56 respondents. Data was collect by using a questionnaire that are closing form. The results are presented in frequency distribution table. Result : Attitudes of klimakterium’s women in the deal of irregular menstrual disorders was positive with a value of 1168 (more than median), in the deal of hot flushes that occur at night was positive with a value of 1230 (more than median), and in the deal sweat a lot during the night day was positive with a value of 1485 (more than median). Conclusion : The attitude of klimakterium’s women of dealing menopause at Jimus Village Polanharjo District Klaten Regency is positive. Tip : If klimakterium’s women have complaints that form an irregular menstrual disorders, hot flushes that occur at night, and sweat a lot at night, consult or check your self to midwife at the health center, BPM, PKD, or when activities posyandu elderly.